The Body Mass Index (BMI) of Human Age and Gender Structure as the Main Cause of Cardiovascular and Nephrotic Diseases (Bangladesh Journal of Medical Science, 2013)
Background: Factors affecting the growth of the organism may be either endogenous, such as genetic factors like genetic heritage, or exogenous such as food, social and health status, physical activity, etc. A factor of great importance for human physical growth is BMI, a parameter defined as the ratio of human body weight and height. Aims:The purpose of this article is to determine the BMI in Macedonias population by analyzing age and gender, and finding the correlation of endogeneous and exogeneous factors and the BMI factor. All measurements were performed at the health facility. Surveys were also conducted for gathering information about gender, age, weight, height, eating habits, socioeconomic status, and education. Results: This clinical research studied 257 patients, 143 males and 114 females. Among other factors involved in this research are blood glucose, fat parameters and potential risk factors for cardiovascular and nephrotic diseases. Conclusions: After the discovery and identification of renal disease, the impact of BMI can be distinguished from pathological processes, such as irregular eating, various inflammations, and changes in the metabolism of vitamin D, etc. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 256-262DOI: http://dx.doi.org/10.3329/bjms.v12i3.12618